2022
DOI: 10.3390/chemosensors10020046
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Oxime-Functionalized IL/16-s-16 Gemini Surfactants System: Physicochemical Study and Structural Transitions in the Presence of Promethazine as a Potential Chiral Pollutant

Abstract: The increasing concern about chiral pharmaceutical pollutants is connected to environmental contamination causing both chronic and acute harmful effects on living organisms. The design and application of sustainable surfactants in the remediation of polluted sites require knowledge of partitioning between surfactants and potential pollutants. The interfacial and thermodynamic properties of two gemini surfactants, namely, alkanediyi-α,ω-bis(dimethylhexadecyl ammonium bromide) (16-s-16, where s = 10, 12), were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Consequently, the outcome of every system has exhibited diverse particle morphologies that self-assemble as a result of a decrease in negative ζ potential values. 57 …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the outcome of every system has exhibited diverse particle morphologies that self-assemble as a result of a decrease in negative ζ potential values. 57 …”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids in general fulfil many of the 12 criteria as a green solvent related to the availability, price, recyclability, synthesis, toxicity, biodegradability, performance, stability, flammability, storage, and renewability [ 8 ]. Ionic liquids can offer a better alternative to volatile solvents, which has led to its massive use in industrial applications such as separation and purification, and as chemical catalysts, biorefinery concepts [ 3 ], extractions [ 1 ] and others [ 9 , 10 , 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids in general fulfil many of the 12 criteria as a green solvent related to the availability, price, recyclability, synthesis, toxicity, biodegradability, performance, stability, flammability, storage, and renewability [8]. Ionic liquids can offer a better alternative to volatile solvents, which has led to its massive use in industrial applications such as separation and purification, and as chemical catalysts, biorefinery concepts [3], extractions [1] and others [9][10][11][12] Recently, research studies have revealed that some of these ILs demonstrate a significant toxicity level [13,14]. Though the toxicity evaluations of ILs have been extensively reported in the literature, biodegradation data are comparatively limited [15].…”
Section: Introductionmentioning
confidence: 99%